Reduction and removal of As(Ⅴ) in aqueous solution by biochar derived from nano zero-valent-iron (nZVI) and sewage sludge. (August 2021) - Liu, Liheng; Zhao, Jirong; Liu, Xiu; Bai, Shaoyuan; Lin, Hua; Wang, Dunqiu
Abstract: Biochar prepared by co-pyrolysis of nano-zero-valent iron and sewage sludge (nZVISB) was used to remove As(Ⅴ) from aqueous solution. When the initial pH was 2, the initial As(Ⅴ) concentration was 20 mg L −1, the dose of nZVISB was 10 g L −1, the contact time was 24 h, and the adsorption temperature was 298K, the removal efficiency of As(Ⅴ) was greater than 99%. The isothermal removal of As(Ⅴ) followed the Freundlich model better, and the maximum adsorption capacity of As(Ⅴ) was 60.61 mg g −1 . The removal process of As(Ⅴ) could be better described by pseudo-second-order kinetic model, and the rate-controlling step should be liquid film diffusion and chemical reaction. Thermodynamic analysis indicated that the removal of As(Ⅴ) was a spontaneous and endothermic process dominated by chemical adsorption. The characterizations of nZVISB before/after adsorption and the solution after adsorption suggested that the iron-containing substances (Fe 0, Fe 2+, FeOOH) and organics in the nZVISB had a great effect on the removal of As(Ⅴ), and the As was mainly immobilized on nZVISB by speciation of As–O–Fe. Highlights: As(Ⅴ) removal followed Freundlich model better, and the qmax of biochar to As(Ⅴ) was 60.61 mg/g. The removal of As(Ⅴ) was better described by pseudo-second-order kinetic model. Liquid film diffusion and chemical reaction together determined the removal rate of As(Ⅴ). The removal of As(Ⅴ) was a spontaneous and endothermic process dominated by chemical adsorption. Fe 0, Fe 2+, FeOOH and organics participated in reduction and removal of As(Ⅴ).